(untitled) (Revista LIDER, 2018)
The Meetings of Argentine and Chilean bishops constituted an activity of joint action before the problem of Chilean immigration in Patagonia. We will analize the first four meetings of Chilean and Argentine bishops (1976 in Bariloche, 1977 in Puyehue, 1978 in General Roca, and 1979 in Puerto Montt), to undertand what were the problems and concerns detected on Chilean migration to Patagonia and possible solutions to jointly create the first binational pastoral migration lines.